Mathematics Operation Card (MOC): Mathematics Operating Number Educational Game Cards for Elementary School Students - Faizah, Hanim; Sulistyaningtyas, Annisa Dwi (Indonesian Journal of Education and Mathematical Science, 2024)
Mathematics is a subject with very abstract material, so the existence of learning media is very necessary. The purpose of this research is to develop an educative game card learning media "Mathematics Operation Card (MOC)" aimed at low-grade elementary school students. The development stage was carried out using the ADDIE model which consisted of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments used in this study were interview guides, observation sheets, student response questionnaires, and learning achievement tests. Based on the results of expert validation and materials as well as limited trials, MOC received a good category that was suitable for use and received positive responses from students. So that MOC can be applied in the process of learning mathematics in class.